Of Alpinists and Domestic and Wild Animals in the Alps (1857-1899): a Corpus Analysis - Samia Ounoughi (Caliban: French Journal of English Studies)
British and Irish alpinists were among the first to explore the highest altitudes in the Alpine massif and to write about it, especially in the second half of the nineteenth century. They reported on their travels and many travel narratives they produced were published in the Alpine Journal. As fauna and flora get scarcer with altitude, there is an increasing number of animal life occurrences in the narratives. They are brief, yet very instructive. Based on corpus linguistics and discourse analysis, I investigate how the presence of animals intervenes in alpinists’ narratives and whether the mere traces of the presence of animals could be construed as encounters. Can such encounters evolve towards a form of affection? In any case, wild animals provide a proof of life in dangerous ascensions. They raise hope or signal danger. Thus they become a key-element in the narratives; they act a significant part in the alpinist’s experience with whom they share a survival instinct that, under such conditions, relates as much to humans as to animals.